2017
DOI: 10.1111/eve.12735
|View full text |Cite
|
Sign up to set email alerts
|

Post‐operative reflux – a surgeon's perspective

Abstract: Summary Post‐operative ileus (POI) is a well‐recognised complication of colic surgery that accounts for a high proportion of post‐operative deaths. Although much has been written about the pathophysiology and management of POI in horses, most studies seem to apply research findings to the clinical case without full regard for the clinical evidence. Although much attention has focused recently on the role of inflammation, this narrow focus might explain our failure to make important advances in managing horses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 84 publications
(221 reference statements)
2
36
0
Order By: Relevance
“…The term post-operative reflux (POR), proposed to describe solely the presence of reflux following surgery without any causal assumptions [20], includes both mechanical obstructions and functional motility inhibition as potential underlying mechanisms. In the interest of clarity, this review will focus on POI; namely, the functional inhibition of motility following abdominal surgery.…”
Section: Equinementioning
confidence: 99%
See 2 more Smart Citations
“…The term post-operative reflux (POR), proposed to describe solely the presence of reflux following surgery without any causal assumptions [20], includes both mechanical obstructions and functional motility inhibition as potential underlying mechanisms. In the interest of clarity, this review will focus on POI; namely, the functional inhibition of motility following abdominal surgery.…”
Section: Equinementioning
confidence: 99%
“…Minimisation of tissue handling is likely to have beneficial effects via reduced induction of inflammation within the muscularis [28,29,37]. However, the potential benefit of limiting the degree of intestinal manipulation in equine surgery must be weighed against the increased risk of POR associated with inadequate decompression of the SI which may result in kinking, and therefore obstruction, of distended SI loops [20]. Studies conducted in rodent models have clearly demonstrated an association between the force of manipulation and both the resulting inflammatory response and the delay in recovery of GIT motility [29].…”
Section: Intestinal Manipulationmentioning
confidence: 99%
See 1 more Smart Citation
“…We agree that future studies with even randomisation into both resection and nonresection groups to account for this variable would be informative. Nonetheless, Dr. Freeman has previously indicated that horses in which SISO is not resected are arguably more critical patients to manage because of the known presence of ischaemic‐injured intestine , so it could be argued that more nonresected cases in the firocoxib group is an allocation bias against that group. The authors are aware of and have discussed prothrombotic side effects of COX‐2 inhibitors in human beings previously . Horses are not known to be susceptible to these prothrombotic side effects of COX selective NSAIDs, and no significant increase in such side effects (such as thrombosed jugular veins) were noted in horses on firocoxib in the present RCT. The authors were careful not to overstate the results indicating that ‘this RCT provides important preliminary evidence that firocoxib offers clinical benefits.’ In the letter by Dr Freeman, the bolded part of the statement was omitted to make a point not intended by the authors.…”
mentioning
confidence: 99%
“…We agree that future studies with even randomisation into both resection and nonresection groups to account for this variable would be informative. Nonetheless, Dr. Freeman has previously indicated that horses in which SISO is not resected are arguably more critical patients to manage because of the known presence of ischaemic-injured intestine [2], so it could be argued that more nonresected cases in the firocoxib group is an allocation bias against that group. • The authors are aware of and have discussed prothrombotic side effects of COX-2 inhibitors in human beings previously [3].…”
mentioning
confidence: 99%